O desenvolvimento do ego infantil expresso nas imagens oníricas de crianças - Fillus, Michel Alexandre (2013)
The present study aimed to observe the expression of children dream, this means selecting for a more accurate analysis, the images pertaining to the archetypes, evidenced in children's productions, which are important in the process of ego development and expansion of consciousness in childhood. It is considered that the archetypes are basic patterns of psychic organization, without content a priori, present from birth, that mediate the experience of children around fundamental issues of human life and are filled with content coming from personal experiences. The population consisted of 55 children, divided into two groups, with four to five years of age, enrolled in a public school located in the metropolitan region of Curitiba. Activities were collecting the dream material of children in school hours, using design as a vehicle for the exhibition of the story of the dream. The method of analysis was qualitative, creating categories of analysis from the material obtained, based on assumptions of Analytical Psychology. It was concluded that the activity with dreams proved to be an effective channel to observe the unconscious dynamics of children, including aspects of the developmental trajectory of ego and consciousness expansion. It was observed that the content of the dream in childhood is not random, but has a sense of being present evidence archetypal mother, father and brother, important in the structuring of the personality, with its specific functions. How organizing element of the initial experiences of autonomy and symbol of the ego, the archetype of the hero was observed in a diffuse form, corresponding to what was named "Hero of the spectrum", including the symbolic unconscious formations that translate into images of shelter and differentiation, collaborative features, aspects instinctive images of confrontation and resistance indicative of individuality